2014
DOI: 10.1021/tx500199b
|View full text |Cite
|
Sign up to set email alerts
|

Identification of trans,trans-2,4-Decadienal Metabolites in Mouse and Human Cells Using Liquid Chromatography–Mass Spectrometry

Abstract: trans,trans-2,4-Decadienal (tt-DDE), a lipid peroxidation product of linolieic acid, is the most abundant aldehyde identified in cooking oil fumes and is readily detectable in food products as well as in restaurant emissions. Previously, we have reported the toxicological effects of tt-DDE in vitro and in vivo. However, the metabolic pathways of tt-DDE in vivo remain unclear. In our present study, we combined liquid chromatography-mass spectrometry with triple quadrupole and time-of-flight to identify tt-DDE m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Trans,trans-2,4-decadienal (tt-DDE), a lipid peroxidation product of linoleic acid, can be oxidized to the two metabolites 2,4-decadienoic acid and cysteine-conjugated 2,4-decadien-1-ol. These have been found in cell culture models and urine of mice gavaged with tt-DDE, using liquid chromatography coupled to tandem mass spectrometry to identify the structures [96]. Carboxylic acid metabolites of HHE (4-hydroxy-2E-hexenoic acid; 4-HHA), HNE (4-hydroxy-2E-nonenoic acid; 4-HNA) and HDDE (4-hydroxy-2E,6Z-dodecadienoic acid; 4-HDDA) were detected in human urine using NICI-MS, and occurred at higher concentrations in aging and diabetes [50].…”
Section: Analysis Of Free Aldehydic Oxidation Products and Their Metamentioning
confidence: 99%
“…Trans,trans-2,4-decadienal (tt-DDE), a lipid peroxidation product of linoleic acid, can be oxidized to the two metabolites 2,4-decadienoic acid and cysteine-conjugated 2,4-decadien-1-ol. These have been found in cell culture models and urine of mice gavaged with tt-DDE, using liquid chromatography coupled to tandem mass spectrometry to identify the structures [96]. Carboxylic acid metabolites of HHE (4-hydroxy-2E-hexenoic acid; 4-HHA), HNE (4-hydroxy-2E-nonenoic acid; 4-HNA) and HDDE (4-hydroxy-2E,6Z-dodecadienoic acid; 4-HDDA) were detected in human urine using NICI-MS, and occurred at higher concentrations in aging and diabetes [50].…”
Section: Analysis Of Free Aldehydic Oxidation Products and Their Metamentioning
confidence: 99%
“…A recent study demonstrated that orally administered 2,4-decadienal was metabolized to 2,4-decadienoic acid and a cysteine-conjugated compound. 19 Unsaturated aldehydes are generated during lipid peroxidation and play critical roles in oxidative stress. 20,21 The structure activity relationship demonstrated in the present study suggests that serotonin-producing enteroendocrine cells sense luminal unsaturated aldehydes to prevent the excess absorption and ingestion of potent peroxides such as unsaturated aldehydes through delaying gastric emptying followed by suppression of appetite.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Because (E,E)‐2,4‐decadienal is highly reactive and exhibits teratogenicity and carcinogenicity, most of the research is focused on DNA damage, [ 13 ] cytotoxic effects on smooth muscle cells, [ 14 ] pulmonary changes, [ 15 ] cytotoxicity to human vascular SMC, [ 14 ] effects on human bronchial epithelial cells, [ 16 ] and mitochondrial dysfunction and oxidative stress [ 17 ] induced by the aldehyde, as well as identification of its metabolites. [ 18 ] However, in the field of food science, most of the research focuses on the monitoring of the formation of (E,E)‐2,4‐decadienal during processing [ 19–22 ] or studying the Maillard reaction of (E,E)‐2,4‐decadienal and amino acids in a heating system. [ 23,24 ] Only a few studies have focused on the reaction of (E,E)‐2,4‐decadienal with proteins; for example, mass spectrometry was used to identify the (E,E)‐2,4‐decadienal‐mediated modification sites in cytochrome c [ 25 ] as well as ribonuclease A and lactoglobulin.…”
Section: Introductionmentioning
confidence: 99%